Carapace shape of some trichodactylidae crabs: Analysis by geometric tools as a possible way of including females in taxonomic differentiation - Giri, Federico (2009)
The family Trichodactylidae characterizes the aquatic environments of the plain, being the Paraná River an important system in the continent. The taxonomic studies of this group were based on carapace ornamentation and male gonopod morphology. THe aim of this study was to explore an alternative way of taxonomic identification of the members of the Trichodactylidae family, including females. This studie focused on the application of geometric morphometric analysis to the carapace of representative species from Middle parana River.